Human genetic resistance to malaria. - Williams, T (Springer New York, 2009)
This brief chapter highlights the need for caution when designing and interpreting studies aimed at seeking new genes that may be associated with malaria protection, or investigating the potential mechanisms for protection in promising candidates. Judging genetic effects on the basis of the wrong clinical phenotype and missing true protective genes because their protective effects are masked by unpredictable epistatic effects are major potential pitfalls. These issues are by no means unique to malaria: in recent years, the importance of larger sample sizes and careful phenotypic definitions have become appreciated increasingly, particularly for genome-wide studies of complex diseases (Cordell and Clayton, 2005; Burton, Tobin and Hopper, 2005). Until recently, research in the field of malaria genetics has not enjoyed the sort of funding afforded to similar work investigating diseases of importance to the developed world. However, in the last few years, coupled with advances in genetic diagnostics that have led to massive automation and falling costs per gene explored, momentum has grown towards more generous funding that brings with it the opportunity for much larger, multisite cohesive studies. The stage is set for a giant leap forward in the coming years.